PERBANDINGAN ANALISIS EKONOMI PERKERASAN ASPAL DAN BETON SEMEN PADA RUAS JALAN UNTUNG SUROPATI DI KOTA SAMARINDA - BAYU PUTRA BJ, ANGGA (KURVA S JURNAL MAHASISWA, 2014)
Based on the economic analysis of asphalt and concrete pavement semenpada Jalan Untung Suropati in Samarinda as follows;1. The amount of budget costs for asphalt pavement physical work (bending) of Rp. 12,461,324,580.65 and cement concrete Rp. 17,097,828,997.602. The amount of costs incurred for the maintenance of asphalt pavements (bending) consists of periodic maintenance and routine maintenance for 25 years of service life with Rp. 56,113,536,085.77 and cement concrete Rp. 11,894,554,291.98 for 25-year service life.3. The results of benefit and cost (B / C) of pavement isa. B / C ratio Pavement bending = Rp. 69,258,377,908.27 /   Rp. 56,113,536,085.77= 1,234> 1 (ok)b. B / C ratio of cement concrete pavement = Rp. 29,372,105,090.60 /                                                                                    Rp. 11,894,554,291.98                                                                     = 2.469> 1 (ok)               Can be compared to B / C ratio for flexible pavements can be used with the assumption that the implementation costs are cheaper but more expensive road maintenance costs while for cement concrete pavement is more expensive but the cost of implementing the long-term effects for 25 years costs more murah.Untuk pemiliharaan Jalan Untung Suropati more either using cement concrete pavement, because many roads impassable large tonnage vehicles, so that road maintenance is not carried out continuously. Need to do a more in-depth studies to policy-makers in this case the government in determining the planning of pavement and be seen aspects of social and environmental sustainability analysis.